Demographic, clinical, and laboratory characteristics of patients with COVID-19 during the second and third waves of the pandemic in Egypt - Ragaey A. Eid; Abdelrahman M. Attia; Mahmoud Hassan; Marwa Abdallah Shaker; Manar Ahmed Kamal (Elsevier, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel virus that belongs to the coronaviruses and causes coronavirus disease 2019 (COVID-19). In this study, we explored the demographic details, clinical features, and routinely conducted laboratory investigations of patients with COVID-19 during the second and third waves of the pandemic to understand their possible diagnostic and prognostic values in Egypt. Methods: In this retrospective cohort study, the demographic characteristics, detailed medical history, laboratory findings, and symptoms of all enrolled patients with SARS-CoV-2 were collected from the medical records of Beni Suef University Hospitals between December 15, 2020, and April 15, 2021. Results: This retrospective study included 473 patients, almost all of whom were elderly. The median age of the patients was 48 years, and those with moderate and severe disease were older than those with mild infections. The proportion of females was higher (63.4%) than males (36.6%). Diabetes mellitus (DM) was the most common comorbidity (17.3%), and fever was the most typical manifestation of COVID-19 (62.6%). Those with severe disease showed a higher C-reactive protein level (CRP) than those with moderate (p-value 0.009) or mild (p-value 0.01) diseases. Serum ferritin levels were significantly higher in patients with severe disease than in those with moderate disease (p-value 0.018). In contrast, d-dimer and serum creatinine were normal and showed no significant difference in all comparisons (p-value overall 0.21). Conclusion: This study observed several variations in COVID-19 patients' characteristics. The new manifestations included skin rash, bone and low back pains, and rigors. In contrast to females, most males had moderate-to-severe illness. Old age and higher body mass index was associated with increasing severity. d-dimer and complete blood count were normal and could not identify potential COVID‐19 patients. Patients who had mild illness were still at risk of developing post-COVID complications.